Analyzing Indonesia’s Inflation in 1998-2020: Error Correction Model Approach - Shaila Farizqiyah; Indah Yuliana (International Journal Labs, 2022)
Inflation is a macroeconomic problem that is of concern, unstable inflation has a negative impact on people's welfare, so inflation control is important. The purpose of this study is to estimate the factors that influence inflation in Indonesia for the period 1998-2020. The research method uses descriptive analysis by providing an overview of the development of inflation, interest rates, exchange rates, household consumption, and GDP in Indonesia during 1998-2020. Quantitative analysis using Error Correction Model (ECM). This study uses secondary data from the Central Statistics Agency (BPS) and Bank Indonesia (BI). The results obtained indicate that all variables (interest rates, exchange rates, household consumption and GDP) simultaneously have a significant effect on inflation, both in the long and short term. Based on the results of the partial test, the interest rate variable has a positive and significant effect on inflation in Indonesia both in the long and short term. The exchange rate variable partially has a negative and significant effect on inflation in Indonesia, both in the long and short term. Furthermore, the GDP variable partially has a positive and significant effect on inflation in the long term but not significant in the short term. Meanwhile, the household consumption variable partially has no significant effect on inflation in Indonesia during the 1998-2020 period.